Developing Madura local content and augmented reality-based digital textbook to improve scientific reasoning ability - Mochammad Yasir; Ana Yuniasti Retno Wulandari; Nur Qomaria; Binar Kurnia Prahani; D. Dwikoranto (University of Muhammadiyah Malang, 2022)
Textbooks currently circulating have not been adapted to online learning systems and their contents are less interactive, less communicative, and have not been based on local content potential. This research aimed to produce digital textbooks based on Madura local content and augmented reality to improve students’ scientific reasoning ability. This research development was done based on ASSURE instructional design, between July and August 2020. This research involved 15 students of SMP Al-Hikam Burneh, Bangkalan-Madura. The assessments of the digital textbook were done to decide its validity, practicality, and effectiveness. Furthermore, the students’ scientific reasoning abilities were measured using pretest and posttest. The validity data obtained were analyzed descriptively using percentages, while students’ scientific reasoning skills were analyzed using gain scores. The results showed that the percentage values were 87.5% for content validity (valid), 91.10% for media (very valid), 87.41% for technical (very valid), and 88.9% for practicality (valid). In addition, the students’ scientific reasoning skills were classified as effective based on the gain scores achieved in each indicator i.e., 0.49 (argumentation), 0.45 (existing knowledge), 0.38 (methodology), 0.43 (analysis), and 0.40 (concluding). Thus, the digital textbook developed is effective to improve students’ scientific reasoning skills.